Characterization of Climate Change Communication: Implication for Environmental Sustainability in Ogba, Egbema, Ndoni Local Government Area of River State, Nigeria - Peace Nwaerema; Nwokezi John Ikoro (Randwick International of Social Science Journal, 2021)
Communicating climate change occurrence in Ogba Egbema Ndoni Local Government Area of Rivers State was the key interest of this study due to the incessant environmental degradation caused by multinational oil and gas companies in the area. This study used multi-stage cluster sampling technique and administered four hundred (400) questionnaires in a study population of 445,760 persons determined by Taro Yamane statistical technique. The findings revealed that the stakeholders felt that climate change really occurred in the area but had not adequately adapted to the impact of climate change with 69.3% showing poor preparedness to climate change adaptation. The radio, television and town-hall meeting were the most effective media of climate change communication, but social media such as WhatsApp, Facebook, Twitter, Instagram, Telegram et cetera were poorly used to communicate climate change phenomenon. Thus, the indigenous town-crying communication medium showed 95% response of disagreement of not being used to inform the stakeholders of climate change occurrence. However, 68% response revealed that the government was not concerned with climate change communication in the area, rather, Non-governmental Organizations (NGOs), Community Based Organizations (CBOs) and the host companies relatively showed concerned in communicating climate change occurrence to the stakeholders. The result indicated that the level of climate change occurrence did not statistically significantly relate with climate change communication in the area. Thus, it was recommended that community stakeholders should have access to weather information, agricultural extension services, educational and school curriculums should integrate climate change communication, indigenous knowledge and communication media should be used as well as government should be serious with issues of climate change communication so as to cushion the effects of climate change impact in Ogba Egbema Ndoni Local Government Area of Rivers State, Nigeria.